Analysis of Halal Certification Renewal Service Quality and Their Effect on the Customer’s Satisfaction and Loyalty in Yogyakarta (Case Study in Meatball Stall) - Jumeri Jumeri; Khosyani; Falah M.A.F (Institute for Halal Industry and System (IHIS) Universitas Gadjah Mada, 2021)
The society awareness in consuming halal, safe, and healthy foodstuff within these past few years kept on increasing. This was closely related to responsible food manufacturers which produced sustain halal foods, as evidenced by ownership halal certification. In order to increase the satisfaction of food producers and to maintain their commitment to extend the halal certificates, the quality of halal authority service should always be enhanced. This study aims to identify the Customer Satisfaction Index (CSI) value, to determine the influence of halal label and product attributes toward customer’s satisfaction and loyalty of meatball stalls in Yogyakarta, and to identify the influence of halal label toward selling volume on certified meatball stalls. The instruments used were questionnaires containing 21 quality attributes of halal certificate renewal service. Analyses were performed using Structural Equation Modeling (SEM). The model was composed of seven latent variables: halal certification, brand, price, taste, service, customer satisfaction and customer loyalty. Result of the research showed that taste and halal certification have significant effect on the customer’s satisfaction and loyalty of certified meatball stalls. Halal certification have affected the certified meatball stalls in Yogyakarta by increasing the selling volume of 25-37.5%.